Tata Bahasa Kasus dalam Novel “Nasiitu Anni Imra’ah” Karya Ihsan Abdul Quddus Berdasarkan Perspektif Charles J. Fillmore / Case Grammar in Ihsan Abdul Quddus' Novel "Nasiitu Anni Imra'ah" Based on Charles J. Fillmore's Perspective - Abdul Basid; Heniatus Zahroh (Diwan : Jurnal Bahasa dan Sastra Arab, 2022)
Case grammar is the result of generative and transformative grammatical faults in the form of a failure to explain the presence of the semantic function of nouns and their association with a verb. This research intends to: (1) disclose the modalities in Ihsan Abdul Quddus' book "Nasiitu Anni Imra'ah" from the viewpoint of Charles J. Fillmore; and (2) identify the proposition in Ihsan Abdul Quddus' novel "Nasiitu Anni Imra'ah" from the perspective of Charles J. Fillmore. This is qualitative descriptive research. The novel "Nasiitu Anni Imra'ah" by Ihsan Abdul Quddus served as the study's data source, and it portrays the story of a lady who aspires to be a political leader. Reading, translation, and note-taking approaches were employed to gather data in this study. In this study, the validation technique is divided into two stages: increasing persistence and peer discussion. The data analysis method is divided into three steps: data reduction, data display, and conclusion. The findings of this study revealed that: (1) the modalities in the novel "Nasiitu Anni Imra'ah" by Ihsan Abdul Quddus based on the perspective of Charles J. Fillmore are the modality of tense and the modality of an adverb; and (2) the propositions in the novel "Nasiitu Anni Imra'ah" by Ihsan Abdul Quddus based on the perspective of Charles J. مستلخص أدى الخطأ النحوي التحويلي التوليدي في شكل عدم القدرة على تفسير وجود الدور الدلالي للاسم وارتباطه بالفعل إلى ظهور نظرية جديدة، وهي قواعد الحالة. تهدف هذه الدراسة إلى اكتشاف الطرائق في رواية "نسيت أني امرأة" لإحسان عبد القدوس على أساس نظرية جرليس ج. فيلمور؛ وتحليل الجر في رواية "نسيت أني امرأة" لإحسان عبد القدوس على أساس نظرية جرليس ج. فيلمور. ونوع هذا البحث وصفي نوعي. ومصدر البيانات هو "نسيت أني امرأة" لإحسان عبد القدوس، والتي تحكي قصة امرأة تطمح إلى أن تصبح رائدة في المجال السياسي. وطريقة جمع البيانات هي تقنية القراءة وتقنية الترجمة وتقنية الكتابة وتقنية تحقق البيانات هي زيادة المثابرة والمناقشة بين الباحثين. نتائج هذه الدراسة هي: وجود نوعين من الطرائق في شكل طرائق الوقت وطرائق الظروف: ووجود أربعة أنواع من الحالات في شكل حالة وكيلة، وحالة موضوعية، وحالة تفسيرية، وحالة زمنية. الكلمات المفتاحية: إحسان عبد القدوس ؛ رواية؛ طرائق